PERKAWINAN PADA GELAHAN (STUDI LEGITIMASI FOLOSOFIS, SOSIOLOGIS DAN YURIDIS PRAKTEK PERKAWINAN PADA GELAHANG PADA MASYARAKAT HINDU BALI) - I Nengah Suastika (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This study aims to examine the philosophical, sociological and juridical foundations as well as the conditions for marriage in gelahang according to Balinese Hindu customary law. This research uses a qualitative type of research. Data collection techniques through interviews, observations, and documentation studies. Data analysis uses qualitative data analysis which begins with data accumulation, data reduction, data presentation and data retrieval. Philosophically, marriage in gelahang is formulated as a belief in the ceritra of the Jaratkaru contained in the Upanisads which states that the deceased person, his spirit will be tormented and cannot be reincarnated if he does not have children. Sociologically the family passed on its descendants by other families has a piscological skates that are difficult to decipher in order to establish harmony. Juridically the legal basis of marriage in gelahang is sloka in Manawa Dharmasastra IX. 118 which declares to the sisters, the brethren shall give some part of their share, each a quarter of its share; those who refuse to give it will be locked. The main conditions of the marriage process in gelahang are not saying goodbye (saying goodbye to ancestors) in the woman's merajan and the existence of a prenuptial agreement. The main conditions of the marriage process in gelahang are not saying goodbye (saying goodbye to ancestors) in the woman's merajan and the existence of a prenuptial agreement. The material for the prenuptial agreement on marriage in gelahang, namely: (1) regarding the answer to the parents, (2) regarding the child, (3) regarding the tangungjawab in the traditional village, (4) regarding the place of burial after death, and (5) regarding the inheritance property.